The Role of YouTube-Based Drawing in Early Childhood Social-Emotional Development - Samsul Alam; Sunarto Sunarto (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The objective of this study is to examine the role of YouTube-based drawing in early childhood social-emotional development. This study employed qualitative research methods to get a comprehensive comprehension and analysis of the subject matter. The chosen research methodology is case study analysis, which involves analysing and interpreting the literature as well as the data acquired via observations, interviews, and documentation. The data in this study were obtained from learners, teachers, children’s artworks, and teacher records such as RPPH and teacher journals. The data in this study were analysed using a child development theory created by CASEL. The study findings indicate that young children who engage in YouTube-based drawing activities actively connect with both their peers and teachers. The act of sketching indirectly contributes to the facilitation of early childhood social-emotional development. The observational data on YouTube-based sketching in early infancy reveals five primary categories of social-emotional competence: self-awareness, self-management, decision-making, interpersonal skills, and social awareness.